Viewpoint: Estimating the Causal Effects of Policies and Programs - Jeffrey A. Smith; Arthur Sweetman (Institute for the Study of Labor (IZA), 2016)
Estimation, inference and interpretation of the causal effects of programs and policies have all advanced dramatically over the past 25 years. We highlight three particularly important intellectual trends: an improved appreciation of the substantive importance of heterogeneous responses and of their methodological implications, a stronger focus on internal validity brought about by the "credibility revolution," and the scientific value that follows from grounding estimation and interpretation in economic theory. We discuss a menu of commonly employed partial equilibrium approaches to the identification of causal effects, emphasizing that the researcher's central intellectual contribution always consists of making an explicit case for a specific causal interpretation given the relevant economic theory, the data, the institutional context and the economic question of interest. We also touch on the importance of general equilibrium effects and full cost-benefit analyses.
Keywords: C18; C21; C26; C50; C90; 330; causal effects; heterogeneous treatment effects; partial equilibrium identification